Salt acclimation induced salt tolerance in wild-type and abscisic acid-deficient mutant barley - Zhiyu Zuo; Junhong Guo; Caiyun Xin; Shengqun Liu; Hanping Mao; Yongjun Wang; Xiangnan Li (Plant, Soil and Environment, 2019)
Salt acclimation is a process to enhance salt tolerance in plants. The salt acclimation induced salt tolerance was investigated in a spring barley (Hordeum vulgare L.) cv. Steptoe (wild type, WT) and its abscisic acid (ABA)-deficient mutant Az34. Endogenesis ABA concentration in leaf was significantly increased by salt stress in WT, while it was not affected in Az34. Under salt stress, the salt acclimated Az34 plants had 14.8% lower total soluble sugar concentration and 93.7% higher sodium (Na) concentration in leaf, compared with salt acclimated WT plants. The acclimated plants had significantly higher leaf water potential and osmotic potential than non-acclimated plants in both WT and Az34 under salt stress. The salt acclimation enhanced the net photosynthetic rate (by 22.9% and 12.3%) and the maximum quantum yield of PS II (22.7% and 22.0%) in WT and Az34 under salt stress. However, the stomatal conductance in salt acclimated Az34 plants was 28.9% lower than WT under salt stress. Besides, the guard cell pair width was significantly higher in salt acclimated Az34 plants than that in WT plants. The results indicated that the salt acclimated WT plants showed a higher salt tolerance than Az34 plants, suggesting that ABA deficiency has a negative effect on the salt acclimation induced salt tolerance in barley.